Case Report: Loss-of-function TRPM4 mutation p.L91Δ implicated in progressive cardiac conduction defect - Hämmerli, Anne-Flore; Ross-Kaschitza, Daniela; Arullampalam, Prakash; Shestak, Anna; Jyh-Ming Juang, Jimmy; El Makhzen, Nada; Ricciardi, Bianca Sol Soloaga; Bokhobza, Alexandre François Edmond; Rougier, Jean-Sébastien; Zaklyazminskaya, Elena V.; Gajek, Jacek; Hasdemir, Can; et al. (Frontiers in Physiology, 2025)
BackgroundThe calcium-activated non-specific cation channel TRPM4 mediates membrane depolarization in many cell types, including cardiomyocytes and Purkinje cells. Rare genetic alterations in the TRPM4 gene can cause familial cases of progressive cardiac conduction defects (PCCDs).Methods and resultsGenetic testing was performed using whole-exome sequencing (WES). Modified human embryonic kidney cells overexpressing either wild-type or the variant p.L91Δ of human TRPM4 were used to investigate the biochemical and functional consequences of this deletion. Western blot and biotinylation experiments revealed a significant reduction in the expression of the mutant channel compared with the wild-type. Functional experiments using the patch-clamp approach demonstrated a significant decrease in TRPM4 current, consistent with the biochemical observations.ConclusionThe new TRPM4 in-frame deletion, p.L91Δ, identified in two unrelated patients with a consistent phenotype, causes a significant decrease in channel expression, leading to its loss of function in the heterologous expression system. These findings further exemplify the role of TRPM4 in genetic cardiac channelopathies.